The Future Liver Remnant in Patients Undergoing the Associating Liver Partition with Portal Vein Ligation for Staged Hepatectomy (ALPPS) Maintains the Immunological Components of a Healthy Organ - Anantha, Ram Venkatesh; Shaler, Christopher Ryan; Meilleur, Courtney Erin; Parfitt, Jeremy; Haeryfar, S. M. Mansour; Hernandez-Alejandro, Roberto (Frontiers in Medicine, 2016)
Background and Aims: A short-interval, two-stage approach termed associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) increases the number of patients with extensive malignant disease of the liver and a small future liver remnant (FLR) that can undergo liver resection. While this approach results in accelerated liver hypertrophy of the FLR, it remains unknown whether this phenomenon is restricted to liver parenchymal cells. In the current study, we evaluated whether ALPPS alters the immunological composition of the deportalized lobe (DL) and the FLR. Methods: In this prospective, single-centre study, liver tissue from the DL and the FLR were collected intra-operatively from adult patients undergoing ALPPS for their liver metastases. The extent of hypertrophy of the FLR was determined by volumetric helical computed tomography. Flow cytometry and histological analyses were conducted on liver tissues to compare the frequency of several immune cell subsets, and the architecture of the liver parenchyma between both stages of ALPPS. Results: A total of 12 patients completed the study. Histologically, we observed a patchy peri-portal infiltration of lymphocytes within the DL, and a significant widening of the liver cords within the FLR. Within the DL, there was a significantly higher proportion of B cells and CD4+ T cells as well innate-like lymphocytes, namely mucosa-associated invariant T (MAIT) cells and natural killer T (NKT) cells following ALPPS. In contrast, the frequency of all evaluated immune cell types remained relatively constant in the FLR. Conclusions: Our results provide the first description of the immunological composition of the human liver following ALPPS. We show that following the ALPPS procedure, while the immune composition of the FLR remains relatively unchanged, there is a moderate increase in several immune cell populations in DL. Overall, our results support the continued utilization of the ALPPS procedure.